The Political Identity of Islam in Indonesia - Rizki, Muhammad Fauzi; Hakiki, Muhamad Ilham Nur; Hidayah, Muhammad Rizal Arifin; Al Hasan, Qasim; Sinka, Valina (Candidate: Jurnal Sains Politik, 2023)
This study focuses on the phenomenon of Islamic identity politics. This phenomenon is common in Indonesia because Indonesia is Muslim in that it has the largest population. The purpose of this study is to explain how Islamic identity politics is widespread in Indonesia’s political struggle over majority elections. The method used is a qualitative research method or a literature search. Studies show that Islamic identity politics has historically arisen from multiple groups competing to emphasize their existence. The feeling that Indonesia is dominated by Islam, which highlights the intersection of nationalism and religious groups, is fundamentallyÂ different from the concept of the state where Pancasila is the supremacy of the state, and thinks that religion is set aside. And that is the issue of identity politics. Another insight explains that the political elite approaches religious figures before the campaign to gain a majority vote to gain power. From this we can conclude that Islam’s political identity will continue to be encountered by the general public, either on a daily basis or with some dynamics. The recommendations of this study are that every human being should have a unique identity, which should be a cohesive element, which is in the interests of the political elite to make propaganda and election interests. It means that it should only be used.